The Effect of Body Posture on Foreign Language Anxiety - Suleyman Kasap; Fuat Tanhan (Sakarya Üniversitesi Eğitim Fakültesi Dergisi)
The Effect of Body Posture on ForeignLanguage AnxietyAbstractSome people of an anxiousdisposition have the tendency to enter aclosed body posture while communicating with others, which is often seen as aphysical response to their mental distress caused by the performance of thisaction. This closed posture, as itcontinues, has been show to further affects the anxiety felt by the speaker,feeding into their worries and forming a cycle of anxiety and difficulty in communication.Given that body posture is a factor in this cycle, if the posture is altered toa more positive form it is expected that the speaker will be less affected byanxiety potential reduction in may lead to improvements in the ability tocommunicate. The aim of this study is to examine whether the language and generalanxiety scores of ELT third-year students changed depending on their bodyposture and accordingly whether adopting high- vs. low-power poses can improve an individual‘s English speaking performance. In this study,the students' bodies were altered into ‘open’ postures, and the effect of thisposture on the students' general anxiety and language anxiety levels wasexamined through the General Anxiety Scale and the Foreign Language AnxietyScale, as well as through semi-structured interviews conducted with theparticipants. The study concluded that changing the body posture to an open style hada positive effect both on foreign language anxiety and on general anxiety.Moreover, the qualitative analysis of the interview protocols revealedconsistency between the perception of the students about their speakingperformance and their anxiety levels. Key words: body posture,foreign language anxiety, general anxiety.1. Asst. Prof. Dr, Van Yuzuncu Yil University, Departmentof ELT , Van, Turkey kasap_hakan@hotmail.com 2.Assoc. Prof. Dr,Van Yuzuncu Yil University, Department of Counselling and PsychologicalCounselling , Turkey fuad65@gmaill.com